SYNTACTICAL ERRORS OF NARRTIVE ESSAY MADE BY EFL STUDENTS LOW ACHIEVEMENTS - Habibah Setyaji; Muh Fajar; Heny Sulistyowati (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
This research aims to find syntactic errors and factors of errors made in the essay narrative in semester V. The method used in this study is qualitative, and the approach used in this research is descriptive research. Data was obtained through documentation and analyzed using Surface Strategy Taxonomy. This research took data based on the category of grades B and C. The results showed that there were four types of errors made by students in descriptive writing. The total errors were 41 errors which were divided into 42% error misinformation, error addition of 35%, error addition 19%%, and misconception misordering as much as 4%. Based on data analysis, a standard error made by students is misformation. In the results of the error factor, the researcher found the most errors in the intralingual error factor.Students are still influenced by their habits in making sentences using their mother tongue (Indonesian). Students make errors in writing, especially in the use of tenses. Most of the students wrote incomplete and ungrammatical sentences. The teacher should find the best method based on the condition of the students to teach English, especially in teaching tenses. Since tenses and grammar are essential for language learning, they should be taught cohesively.